Printed circuit board drilling machine using recyclables (2018)
The implementation of a printed circuit board (PCB) drilling machine using recyclable materials and computer-aided control is presented. A mechanical system using a DC motor for movement on the X and Y axes, and a transmission mechanism by belts, pulleys, and a worm screw was made. For the Z axis, a mechanism based on a worm screw, nuts, and a stepper motor was implemented. The main board has two microcontrollers communicating in a master-slave configuration via a serial protocol. A real-time operating system (OSA) was implemented to optimize the data flow to the computer using the USB protocol, for communication with the slave microcontroller, positioning the Cartesian axes, and control the motors. The slave is responsible for monitoring the status of the encoders and limit switches, as well as the information delivery to the master. A Matlab-based user interface was developed to determine the coordinates of the holes to be drilled by processing a jpg image. This also allows the user to control the DC motors using PWM signals via configurable parameters of PID controllers. The end result is a drilling machine which able to operate both manually and via a computer, for drilling PCBs of a maximum size of 24 × 40 cm. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.